2009
DOI: 10.2337/db08-1794
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein B but not LDL Cholesterol Is Associated With Coronary Artery Calcification in Type 2 Diabetic Whites

Abstract: OBJECTIVEEvidence favors apolipoprotein B (apoB) over LDL cholesterol as a predictor of cardiovascular events, but data are lacking on coronary artery calcification (CAC), especially in type 2 diabetes, where LDL cholesterol may underestimate atherosclerotic burden. We investigated the hypothesis that apoB is a superior marker of CAC relative to LDL cholesterol.RESEARCH DESIGN AND METHODSWe performed cross-sectional analyses of white subjects in two community-based studies: the Penn Diabetes Heart Study (N = 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 51 publications
(89 reference statements)
4
58
2
Order By: Relevance
“…APOB protein is a component of chylomicrons, low-density lipoproteins (LDL), very low-density lipoproteins (VLDL), intermediate density lipoproteins (IDL) and functions as the main protein for transporting cholesterol to peripheral cells [1][2][3][4][5][6] . The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…APOB protein is a component of chylomicrons, low-density lipoproteins (LDL), very low-density lipoproteins (VLDL), intermediate density lipoproteins (IDL) and functions as the main protein for transporting cholesterol to peripheral cells [1][2][3][4][5][6] . The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…The plasma concentration of APOB protein reflects the total number of potentially atherogenic particles 2,4 and, therefore, is predictive of high risk of coronary heart disease that may not be otherwise detected from routine lipid profile 2,[7][8][9][10] . High APOB protein level in blood is correlated with cerebrovascular and coronary artery diseases as well as increased risk of diabetes 1,3,11,12 . Variable number of tandem repeats (VNTRs), also known as minisatellites, comprise a significant portion (~3%) of the human genome 13 .…”
Section: Introductionmentioning
confidence: 99%
“…[203][204][205][206][207][208][209][210][211][212][213][214][215][216] In the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) Study, an autopsy study of 15-to 34-year-old individuals who died of non-CVD causes, non-HDL-C was correlated with fatty streaks and raised lesions in the right coronary artery. 204 In adults, non-HDL-C correlates with coronary calcification 205,206 and CVD progression. 207 Although the relationship between non-HDL-C and CVD outcomes has been studied less extensively than the relationship between LDL-C, myocardial infarction, and cardiovascular death, there are prospective studies that have demonstrated strong relationships between non-HDL-C levels and CVD events in the absence 208 -210 or presence 211,212 of preexisting CVD or acute coronary syndrome.…”
Section: Non-hdl-cmentioning
confidence: 99%
“…Thus, the superiority of non-HDL-C over LDL-C as a CHD risk may be a common phenomenon beyond ethnic, anthropometric and metabolic diversities. Elevated non-HDL-C has been considered a predictor of the development of CHD because the amount of circulating atherogenic lipid particles can be more faithfully reflected in serum non-HDL-C than LDL values 25) , especially in patients with diabetes 26) . In other words, elevation of non-HDL-C is most likely causal for, rather than a simple marker of, CHD.…”
Section: Discussionmentioning
confidence: 99%